PENGARUH PENAMBAHAN VITAMIN C TERHADAP PERFORMA AYAM BROILER SAMPAI UMUR 14 HARI - Supranoto Supranoto (Fakultas Peternakan Universitas Wijaya Kusuma Purwokerto, 2021)
Vitamin C acts as an antioxidant and anti-stress agent that may improve broiler performance during the early growth phase. This study aimed to determine the effect of vitamin C supplementation in drinking water on broiler performance up to 14 days of age. A total of 100 day-old chicks were arranged in a Completely Randomized Design (CRD) consisting of four treatments and five replications, with five birds per experimental unit. The treatments were P0 (without vitamin C/control), P1 (250 ppm), P2 (500 ppm), and P3 (750 ppm) of vitamin C in drinking water. The observed variables were feed consumption, final body weight, and feed conversion ratio (FCR). Data were analyzed using analysis of variance (ANOVA) followed by Duncan's multiple range test. The results showed that vitamin C supplementation had no significant effect (P>0.05) on feed consumption, but had a significant effect (P